ENT600 : Smart Corset / Maisarah Zul ... [et al.] - Zul, Maisarah; Musa, Syamimi; Abdussalam, Siti Nurul Hidayu; Rapie, Nurul 'Ain; Othman, Azlindahani (2018)
Our product is known as Smart Corset. In the market, there is huge lumbar support product but still the worker having back pain. We decide to come up with an innovation to prevent further back pain and also as awareness tool in bending the trunk whenever worker want to do activities such as lifting or carrying. Smart Corset can prevent the incorrect posture by monitoring the posture of lumbar spine within safe range 40° - 45°degree. Smart Corset is use to prevent worker from back injury by using awareness sensor indicator of proper body posture. Another good thing is it also use for patient to reduce recurrent symptoms that will occur rapidly and to prevent symptoms from become severe.